The Livelihood Vulnerability of Vannamei Shrimp Culture as the Impact of Climate Change in Banyuwangi Regency, East Java Province, Indonesia - Setyaningrum, Ervina Wahyu; Yuniartik, Mega; Yuniari, Shinta Hiflina (Faculty of Fisheries and Marine Universitas Airlangga, 2024)
Abstract During Covid-19 outbreak, the production of the Vannamei Shrimp (Litopenaeus vannamei) actually increased and even increased the value of Indonesia's exports. The existence of shrimp culture is closely related to the nature of the surrounding environment, especially climate change. Climate change has a potential impact on aquaculture production, which affects livelihoods that depend on aquaculture. This study aims to analyze the development of sea surface temperature (SST) and high tides over the last 10 years and to analyze the vulnerability of the vannamei shrimp culture to climate change. This research uses a descriptive method. Data were collected through direct interviews with respondents, while the model was a structured interview. Secondary data were obtained from satellite imagery through geographic information systems, and from literature. Data analysis used spatial analysis with Geographic Information Systems (GIS), and vulnerability analysis was carried out to build the Livelihood Vulnerability Index matrix. The results show that climate change affects the development of sea surface temperature (SST) and high tides on the coast of Banyuwangi Regency, East Java Province, Indonesia. It is proven that during the last 10 years SST and high tide data shows that it fluctuates every year, SST between 27.75-29.6°C, the high tide between 1.47-1.57 m. Changes in SST affects high tide, and both become variability that affects vannamei shrimp culture. The results of the vulnerability analysis show that vannamei shrimp culture livelihoods in Banyuwangi Regency are categorized as vulnerable to climate change, with a value of 3.30 (3.34 vulnerability threshold). Highlight Research 1. Climate change affecting livelihood vulnerability of vannamei shrimp culture